Design and testing of a monopropellant thruster based on N2O decomposition in Pd/Al2O3 pellets catalytic bed. (March 2021) - Di Martino, G.D.; Gallo, G.; Mungiguerra, S.; Festa, G.; Savino, R.
Abstract: The aim of the present paper is the investigation of a monopropellant engine based on the exothermic decomposition of nitrous oxide, as a "green" substitute of the most common but highly toxic hydrazine-based systems. First, a general procedure for the design of such a system, in terms of sizing of the catalytic chamber and of the nozzle for prescribed mission requirements, is defined. This procedure is applied for the design of an 800-mN-class thruster prototype, with catalysts based on palladium as active phase on alumina pellets support. Such prototype is experimentally tested highlighting first the nitrous oxide decomposition behavior and issues related to an optimization of system thermal insulation for reducing energy losses. Finally, the measured engine performance are presented and discussed, including a comparison with the results obtained with the same system in a cold-flow operation mode, showing the gain in terms of increased specific impulse and reduced propellant consumption due to the exploitation of the thermal energy obtained from nitrous oxide decomposition. Highlights: A procedure for preliminary design of low-thrust monopropellant rockets is defined. A thruster prototype based on nitrous oxide catalytic decomposition is designed. Experimental tests are carried out varying the catalytic bed loading. Decomposition behavior and engine performance are presented and discussed.